2016
DOI: 10.1049/iet-map.2016.0743
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Wide‐angle broadband microwave metamaterial absorber with octave bandwidth’

Abstract: This comment demonstrates that in a recent study by Bhattacharyya et al., a linear reflective polarisation converter is erroneously interpreted as broadband absorber. It is clearly shown that the incident electromagnetic wave is reflected with its orthogonal polarisation state due to which co‐polarised reflection is reduced. Total absorption, when both the co‐ and cross‐polarised reflected components are considered, is less than 20% in the operating band claimed by the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…However, in these papers authors ignored crosspolarization effect and interpreted phenomenon as absorption. This fact is addressed by the comments, respectively, and article …”
Section: Numerical Simulation Results and Discussionmentioning
confidence: 99%
“…However, in these papers authors ignored crosspolarization effect and interpreted phenomenon as absorption. This fact is addressed by the comments, respectively, and article …”
Section: Numerical Simulation Results and Discussionmentioning
confidence: 99%
“…However, on further investigations, it was found that the broadband absorption resulted from ignorance of cross-polarized reflections from the structures. This fact is addressed by the articles respectively [7][8][9][10][11]. In subsequent section, study and investigations are carried out on the structure proposed in [12], and it is shown that already reported structure is not a metamaterial absorber.…”
Section: Introductionmentioning
confidence: 92%
“…In this context, Metamaterial Absorbers (MAs) offer novel features such as low thickness, nearly perfect absorption and flexibility for tuning of resonant frequency [6]. However, the MAs have disadvantages such as narrow bandwidth owing to the formation of resonating structure, and polarization conversion due to the absence of resistive components [6,7].…”
Section: Introductionmentioning
confidence: 99%